(3EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes - (3GdYeGOj, nCoHh GdoqSoYhO, eMeO Hf eMeO Hf eUWai, J (B982(3g`s
(3ChdgG (B:s
(3CdeQ GSe ddShQI heMdg GdQaY Ydi Cfg NHQ deHJOC eMPha , Cj gPg GdUhQI eSeGI HgPG GdGSe hgh CXgQ ef GdQaY Ydi GdGHJOGA EP de jSHb GdYde HGdJSejI ceG eQ eQGQG hbhdg JYGdi (B: (3Jdc Ydi GdhLg GdGhd eHJOC eSJbd hYdi GdhLg GdKGfj eHJOC KGfs
(3BNQgG (B:s
(3bGd GdYHO GdPdjd eJVQYG Edi QHg GdLdjd hGMTQfj eY GdPjf GfYeJ Ydjge ef GdfHjjf hGdUOjbjf hGdTgOGA hGdUGdMjf hMSf ChdFc QajbG hUdi Gddg Ydji SjOfG eMeO hYdi Bdg hUMHg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 59s
(3eYLe GdeDdajf (B3 / 693s
(3cTa GdXfhf (B1 / 65s
(3TPQGJ GdPgH (B8 / 398s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs